Indicators of intention to use Massive Open Online Courses for academic purposes among IIUM students - Tahiru, Mukaramatu (Kulliyyah of Education, International Islamic University Malaysia, 2017)
This study attempted to determine IIUM postgraduate students' adoption of new educational technologies by examining a set of factors that influence their intention to use Massive Open Online Courses (MOOCs) for academic purposes. Based on Rogers' Diffusion of Innovation and Davis' Technology Acceptance Model, a model was developed and tested to examine the students' intention to use MOOCs for academic purposes. Five precursors (awareness knowledge, how-to knowledge, actual usage, perceived usefulness, and attitude) of intention to use MOOCs for academic purposes were presented in the model. The research questions concentrated on the extent of IIUM postgraduate students' awareness knowledge, how-to knowledge, perceived usefulness, attitude towards MOOCs, actual usage, and intention to use MOOCs for academic purposes. It also explored the significant difference between MOOCs users and non-users in their intention to use MOOCs for academic purposes. It again explored the influence of awareness knowledge, how-to knowledge, perceived usefulness, actual usage, and attitude on intention to use MOOCs for academic purposes. The analysis procedure made use of descriptive statistics, independent sample t-test, and multiple regression analysis. The findings reveal that majority of the respondents do not have awareness knowledge and how-to knowledge. It also shows very few respondents have actual usage of MOOCs. However, majority of the respondents have positive attitude towards MOOCs and majority of them show their intentions to use MOOCs for academic purposes. In addition, the results show a significant difference between users and non-users of MOOCs in their intentions to use MOOCs for academic purposes. It again indicated that all predictor variables significantly contribute to the prediction of intention to use MOOCs for academic purposes except how-to knowledge and actual usage. It also reveals that students' intention to use MOOCs for academic purposes is raised by the perceived usefulness which reflects in their attitude. Awareness knowledge in turn incline the perceived usefulness of MOOCs to students signifying that a substantial amount of knowledge of MOOCs is a precursor to higher level of intention to use. The study reveals a vital implication on how IIUM ought to scheme policies to increase adequate awareness of MOOCs and more importantly its usefulness to students.